PROKRASTINASI MENULIS SKRIPSI DI KALANGAN MAHASISWA SEBAGAI SUMBER GAGASAN BERKARYA KOMIK "CATATAN AKHIR KULIAH" - Lisna Siti Rohaeni, - (2022)
LISNA SITI ROHAENI (1503426). PROCRASTINATION OF THESIS WRITING AMONG UNIVERSITY STUDENTS AS A SOURCE OF COMIC WORKING IDEAS "COLLEGE END NOTES". Thesis of Creation, Department of Fine Arts Education Study Program, Faculty of Art and Design Education, University of Education Indonesia, Bandung 2022 This research is motivated by the phenomenon of academic procrastination experienced by university students in college when writing a thesis as one of the obligations to achieve an undergraduate degree. The Phenomenon has become the focus of the problem as a source of ideas for comic work. This study aims to represent the problem of procrastination in comic works. The creation method used in this research is a Design Thinking theory, started with emphatize until prototype phase. The scope of the story is about the period of final semester of university students. This study uses a narrative inquiry approach to tell the findings in the form of comics, collecting data through case studies and literature studies related to academic procrastination. The prototype phase is using a hybrid technique by going through the following processes: 1) Synopsis making; 2) Storyline creation; 3) Creation of character designs; 4) Storyboarding; 5) Inking through a digital process; 6) Coloring; 7) Giving word balloons. This stage will produce a comic book entitled "College End Notes" with 74 pages. Based on the results of making comics, it can be seen that the process of making comics with hybrid techniques simplify the process of working on works because it utilizes digital technology to process the comic sketches coupled with interesting ideas of comic story would greatly affect the reader‟s impression of enjoying a comic. Visualization "College End Notes" comics is strongly influenced by the characteristics of Japanese comic with a semi-realist drawing style. The recommendation in this research is to continue making a new series of comics about procrastination by making a sequel in which describe a ways that can be used to further prevent academic procrastination on thesis writing. Keywords: Academic Procrastination, Thesis Writing, University Students, Comic Making of "College End Notes"